2017
DOI: 10.1007/978-3-319-69535-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Pain Medications and Male Reproduction

Abstract: The increasing use of opioid medications has become a crisis in developed countries. The profound negative effects of opioids on male reproduction are well known, but this topic is absent from the current conversations about these medications. In the fertility clinic, a significant proportion of our patients are using opioids for pain management, and the options for these men are unclear. Opioids exert their negative effects by a variety of mechanisms. At high doses, testosterone levels fall significantly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…The Delta opioid receptor ( dop ) is enriched in LH cells in males (Log2(fold change) = 1.9). Opioids regulate pain, behavior, and appetite, and are considered to have negative effects on LH secretion in mammals [ 110 , 111 ]. In fish on the other hand, opioid action on LH secretion can be contradicting and was suspected to affect the hypothalamic control of LH secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The Delta opioid receptor ( dop ) is enriched in LH cells in males (Log2(fold change) = 1.9). Opioids regulate pain, behavior, and appetite, and are considered to have negative effects on LH secretion in mammals [ 110 , 111 ]. In fish on the other hand, opioid action on LH secretion can be contradicting and was suspected to affect the hypothalamic control of LH secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The negative effects of opiates are legion, and their effects on male reproduction are well known [ 93 ]. However, there seems to be a general lack of awareness among healthcare professionals regarding the potential for CH in male users of opiates, and this discussion is often absent during clinically-based treatments with opiate therapies, including those discussions with patients [ 93 ]. In a recent systematic review and meta-analysis of opiate effects on the HPG axis, de Vries and colleagues identified 52 studies from the literature, with >18,400 subjects [ 94 ].…”
Section: Signals From the Outside: Morphine Anabolic-androgenic Steroids Physical Trauma And Stressmentioning
confidence: 99%
“…Opioid-induced androgen deficiency (OPIAD) is commonly reported in association with opioid therapy 41,42. Noteworthy, it has been suggested that drugs characterized by dual activity, such as tapentadol, may be associated with a more favorable pattern of endocrine-related toxicity 42.…”
Section: Toxicities Of Special Interestmentioning
confidence: 99%
“…Opioid-induced androgen deficiency (OPIAD) is commonly reported in association with opioid therapy 41,42. Noteworthy, it has been suggested that drugs characterized by dual activity, such as tapentadol, may be associated with a more favorable pattern of endocrine-related toxicity 42. Eichenbaum et al evaluated the effects of tapentadol in healthy male volunteers versus placebo and morphine and in patients with osteoarthritis, compared with placebo and oxycodone 41.…”
Section: Toxicities Of Special Interestmentioning
confidence: 99%